Oppositions in the conceptual and linguistic category of time - Merkibayev, Tulegen; Seisenbayeva, Zhanar; Bekkozhanova, Gulnar; Koblanova, Aiman; Alikhankyzy, Guliya (Opción, 2019)
The article analyzes the representation of oppositions in conceptual and linguistic category of time. The field approach to the analysis of semantic and metaphorical oppositions has been applied here in order to research the category of tense. The nuclear conceptual and semantic oppositions, their national linguistic peculiarities connected with polychronism and monochronism of the examined cultures are defined. In lexical and phraseological "representation of time" the metaphorical component is allocated with such models as "time – eternity"; "time – river/water"; "time – space"; "time – man"; "time – female"; "time – animal" where the binary nature of human perception of surrounding reality is also exhibited.